Produção de sementes de soja na cooperativa agroindustrial CONSOLATA LTDA. Unidade de Cafelânia, PR - Meireles, Ronaldo Bernardon (2008)
The seed producer enterprises need to be feasible to keep themselves in the market. The evaluations about the proceeding methods of production are necessary. By this way the work had the objective of studying the evolution of soybean seed production at the Cooperativa Agruindustrial Consolata Ltda. In order to make this study historic data of the production and the processing and commercial of the seed was taken, from the year 2002/03 to 2006/07. The parameters, evaluated for each year, were: received seed volume, loss during their processing (based on the discharged material), low quality seed lot and commercialized seed lot. The data have been appreciated in percentage for five classes of germination and varietal purity and three physical purity classes. The results led to the following conclusions: the seed producer fields performances could be higher, demanding an intensification at the internal quality program. Still, there s a certain necessity of adopting more adequate techniques to make the seed production and the efficiency at the processes even better. Seed commercialization was about 100% in terms of seed lots approved.